Rate control versus electrical cardioversion for atrial fibrillation: A randomised comparison of two treatment strategies concerning morbidity, mortality, quality of life and cost-benefit - the RACE study design - van Gelder, I.C. (2002)
BACKGROUND: Persistent atrial fibrillation (AF) does not terminate spontaneously and may cause left ventricular dysfunction and thromboembolic complications. For restoration of sinus rhythm electrical cardioversion (ECV) is most effective. However, AF frequently relapses, necessitating re-ECV and institution of potentially harmful antiarrhythmic drugs. If AF is accepted, rate control and prevention of thromboembolic complications using negative chronotropic drugs and warfarin is pursued. It is our hypothesis that rate control therapy is not inferior to ECV therapy in preventing morbidity and mortality. METHODS: RACE (RAte Control versus Electrical cardioversion for atrial fibrillation) is a randomised comparison of serial ECV therapy (repeat ECV as soon as possible after a relapse and institution of an antiarrhythmic drug: sotalol, class IC drug and amiodarone) and rate control therapy (resting heart rate <100 bpm using digitalis, calcium channel blockers and/or β-blockers) in patients with persistent AF. Morbidity (heart failure, side effects of drugs, thromboembolic complications, bleeding and pacemaker implantation), mortality, quality of life and cost-effectiveness are primary and secondary endpoints. Included are patients with a recurrence of persistent AF, present episode <1 year and a maximum of two previous successful ECVs during the last two years. This study is a multicentre study in 31 centres throughout the Netherlands. All 520 patients have now been included. Follow-up is two years. The results are expected this year.